Manganese removal efficiencies and bacterial community profiles in non-bioaugmented and in bioaugmented sand filters exposed to different temperatures. (August 2020) - Ciancio Casalini, Lucila; Piazza, Ainelén; Masotti, Fiorella; Pacini, Virginia A.; Sanguinetti, Graciela; Ottado, Jorgelina; Gottig, Natalia
Graphical abstract: Highlights: Bacteria that oxidize Mn at low temperatures, improve Mn removal in this condition. Bioaugmentation is mainly important at low temperatures. Biofilter microbiomes are more influenced by temperature than by bioaugmentation. Abstract: Biological sand filtration systems are widely used to remove Manganese (Mn) from groundwater. Different experiences have demonstrated that low environmental temperatures decrease the performance of these systems. In order to overcome this problem, in a previous work, a Pseudomonas sagittaria strain named MOB-181, that showed high Mn(II) oxidation and biofilm formation capacities when grown at low temperatures, was isolated. Here, the impact of summer and winter temperatures on Mn removal efficiencies and on bacterial community profiles of both, non-bioaugmented and MOB-181 bioaugmented sand filters, was analyzed. Under summer conditions, MOB-181 inoculated columns showed the best Mn removal performance, removing Mn from the first day of system operation with an efficiency of 27%; also these columns reached an optimum Mn removal efficiency (95%) earlier than control columns (23 days and 29 days, respectively). Under winter conditions, the 27% efficiency was reached earlier for the inoculated columns than for control columns (20 days and 42 days, respectively); and the maximum efficiency (95%) was also reached faster than for the controls (39 days and 54 days, respectively). Bacterial communities profiles were more influenced by temperature changes than by the bioaugmentation process. This work demonstrated the importance of bioaugmentation with the MOB-181 strain to improve Mn removal, by shortening start-up periods, mainly at lower temperatures. Moreover, the obtained data will improve the knowledge on bacterial communities ecosystem involved in Mn removal at different temperatures and should help in developing novel bioaugmentation strategies for the optimization of biological groundwater treatment plants.